mSphere of Influence: Interferon Ultra Is a Means To Fight Viral Disease - Connor G. G. Bamford (American Society for Microbiology, 2020)
ABSTRACT Connor G. G. Bamford works in the fields of virology and innate immunity. In this mSphere of Influence article, he reflects on how three papers by Manry et al. (J. Manry, G. Laval, E. Patin, S. Fornarino, et al., J Exp Med 208:2747–2759, 2011, https://doi.org/10.1084/jem.20111680), Terczyńska-Dyla et al. (E. Terczyńska-Dyla, S. Bibert, F. H. T. Duong, I. Krol, et al., Nat Commun 5:5699, 2014, https://doi.org/10.1038/ncomms6699), and Schoggins et al. (J. W. Schoggins, S. J. Wilson, M. Panis, M. Y. Murphy, et al., Nature 472:481–485, 2011, https://doi.org/10.1038/nature09907) made an impact on him during a critical stage of his career and how they continue to reinforce why he researches what he does and shape the approaches he takes.